Factor Influencing Job stress during Covid-19: Empirical Evidence from Bank Syariah Indonesia - Masyhuri, Masyhuri; Pardiman, Pardiman; Siswanto, Siswanto (University of Merdeka Malang, 2021)
Research on job stress on employees who carry out work from home is rarely studied, so this research is essential considering that Covid-19 impacts the Indonesian Islamic banking industry. This article aims to analyze work-family conflict mediated by an organizational commitment to job stress at Bank Syariah Indonesia employees. The sample was Bank Syariah Indonesia employees who were scattered in several areas in East Java as many as 197 respondents from various branch offices and units. Questionnaires are distributed via google form as direct data collection from respondents. Furthermore, the data were analyzed using structural equation modeling partial least square (SEM-PLS), which was then used to answer the research hypothesis. The results showed work-family conflict affects employee job stress. Work-family conflict affects organizational commitment, organizational commitment has a significant effect on job stress, and organizational commitment mediates work-family conflict on job stress. Implications for further research suggest comparing job stress during the pandemic and after the pandemic. The theoretical contribution of this research supports conflict theory and scarcity theory which says that stress in one role can limit an individual's ability to fulfill other roles, which will lead to work-family conflict. DOI : https://doi.org/10.26905/jkdp.v25i2.5537